Factor Analysis With The Event Of Gout In The Community Of Lumban Barat Village - Agustaria Ginting; Murni Sari Dewi Simanullang; Graicia Agustina Sihombing (Institute of Computer Science (IOCS), 2021)
Gout is a non-communicable disease that occurs due to the accumulation of crystals in the joints, resulting in an increase in gout levels in the body, and attacks the joints causes the joints become swollen, red skin color, a sensation of heat and pain in the joints. The results of the initial survey find 70 people with gout. The purpose of this study is to analyze factors related to the incidence of gout in people aged 30-60 years at Puskesmas area of ​​Lumban Barat village, Paranginan Humbang Hasundutan district in 2021.The research method used is an analytical observational design with a cross sectional design. The gout prevalence is 23.1%, age group 46-60 (63.5%), gender male (36,5%), obese BMI (47.1%), non-good eating pattern (44, 2%). Based on the chi square analysis, it is found that with the results of the chi square statistical test, the age value is p value 0.013, the gender value is p value 0,010, body mass index p value 0.004, eating patterns p value 0.010, which means there is a relationship between age, gender, body mass index, eating patterns, with gout occurence. The gout proportion in this region is 23.1%. Age, obesity, and not good eating patterns have been shown to be associated with the gout accurence. In this study, increasing age, gender, obesity, not eating patterns have each opportunity, 2,600, 3,267, 3,286, 3,557 times more to experience gout than subjects who are younger, not obese and have a good diet